2018
DOI: 10.1371/journal.pone.0197466
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of risk factors for mild cognitive impairment based on word list memory test results and questionnaire responses in healthy Japanese individuals registered in an online database

Abstract: Although the development of effective therapeutic drugs and radical treatment options for dementia and Alzheimer’s disease (AD) remains urgent, progress in recent clinical trials of AD drugs has been less than adequate. In order to advance the progress of clinical trials, it is necessary to establish more efficient methods of recruitment. In Japan, there are registration systems stratified by mild cognitive impairment and preclinical and clinical stages of early and advanced stage dementia, but there is no reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 16 publications
0
7
0
2
Order By: Relevance
“…However, almost all recent clinical trials of drugs aimed at treating AD have been unsuccessful [ 3 ]. Hence, until effective therapeutic agents are developed, it is important to elucidate the risk factors for dementia onset and adopt interventions, where possible, to change lifestyle and individual patient’s characteristics [ 4 ]. In recent years, to prevent and delay the progression of pathological cognitive decline in older adults, it has been recommended that intervention be initiated at an early stage of AD, such as at the preclinical phase [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, almost all recent clinical trials of drugs aimed at treating AD have been unsuccessful [ 3 ]. Hence, until effective therapeutic agents are developed, it is important to elucidate the risk factors for dementia onset and adopt interventions, where possible, to change lifestyle and individual patient’s characteristics [ 4 ]. In recent years, to prevent and delay the progression of pathological cognitive decline in older adults, it has been recommended that intervention be initiated at an early stage of AD, such as at the preclinical phase [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…The same analysis using linear mixed-effect model identified a question “Are you basically satisfied with your life?” as a contributing factor. The question belonged to the category of “mood.” A cross-sectional study using registry data from the IROOP® [6] identified mood as one of the contributing factors toward cognitive functions. Because social involvement inhibits the development of depression [19] , social engagements and presence of friends to call, in the present study, indicate the presence of social connections, inhibiting the development of depression and acting as a protective factor against cognitive decline.…”
Section: Discussionmentioning
confidence: 99%
“…To date, risk factors for dementia have been identified and discussed previously. We reported that the maintenance of mood, motivation, and basic activities of daily living, and so forth contribute to preventing cognitive decline for a short interval of 6 months [6] . We also advised against the hasty consideration of differences among study results and highlighted the need for further data and continuous monitoring.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Penyakit degeneratif pada lansia terdiri dari beberapa jenis, salah satunya adalah kerusakan saraf otak atau penurunan kognitif (pikun). Berdasarkan penelitian Ogawa, et al (2018) yang dilakukan pada 483 lansia dari usia 60-89 tahun menunjukkan bahwa semakin meningkatnya umur lansia maka fungsi kognitifnya akan semakin menurun.…”
Section: Pendahuluanunclassified